Accuracy Of The One-Stage And Two-Stage Impression Techniques (Journal of Pharmaceutical Negative Results, 2023)
Background: To study accuracy of one- stage and two- stage impression techniques.Materials & methods: A resin laboratory-made model with the first molar was prepared by standard method for full crowns with processed preparation finish line of 1 mm depth and convergence angle of 3-4°. Independent t- test was done. The result was analysed using SPSS software.Results: The mean value of the marginal gap obtained by one-stage impression technique was higher than that of two-stage impression technique. A significant difference was reported between the two impression techniques in mid mesial, distal, and lingual regions and average of all surfaces (p < 0.05).Conclusion: There is higher accuracy for two-stage impression technique than for the one-stage impression technique.